ANALISIS PENGARUH FAKTOR PERSONAL, PENDORONG DAN PENARIK TERHADAP KECENDERUNGAN KEINGINAN BERPINDAH KERJA - Tan, Julyana; Purba, Daris (LPPM Universitas Putera Batam, 2021)
The aim of this research was to observe the impact of push, pull and personal factors on turnover of Tax Consultant Office in Batam. This research uses for primary data collection using questionnaire methods. A self-explanatory questionnaire was distributed among them to find that what the factor is for their turn over from one company to another. This paper utilizes survey data collected from 125 employees of Tax Consultant Office in Batam to test influence of personal, push and pull factors toward turnover intention. Questionnaire was used as survey instrument to collect data personally at the locations of the organizations. Descriptive statistics were performed to test on the data by using SPSS (Statistical Package for the Social Science) version 25. The result of the study showed that personal factors showed that does not effect turnover intention. Meanwhile push and pull factors directly effect to turnover intention. And these three factors (personal, push and pull) simultaneously affect the turnover intention.